1979
DOI: 10.2134/agronj1979.00021962007100020006x
|View full text |Cite
|
Sign up to set email alerts
|

N Uptake and Corn Yield as Affected by Applications of Nitrapyrin with Anhydrous Ammonia1

Abstract: The use of nitrapyrin as a nitrification inhibitor of ammonium fertilizers applied to corn (Zea mays L.) has gained widespread interest. Even though initial nitrification rates are usually decreased by nitrapyrin, its use does not always result in increased grain yield. To evaluate the effects of nitrapyrin applied with anhydrous ammonia on yield and N uptake of corn grown on poorly drained soils, field studies were conducted in Illinois at Urbana, Brownstown, and DeKalb. The soil at Urbana and DeKalb was Typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
23
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 6 publications
5
23
0
Order By: Relevance
“…Although the nitrapyrin treatment did not result in an economic advantage for the spring and split N application treatments, the results indicate that for farmers who continue to fall‐apply N, there is a positive economic return for using nitrapyrin. However, a number of other studies have found no significant yield effect nor economic advantage with the use of nitrapyrin (Hendrickson et al, 1978; Touchton et al, 1979; Blackmer and Sanchez, 1988). The variable results with nitrapyrin use are probably due to differences among factors affecting the microbial process of nitrification (e.g., climate and soil type).…”
Section: Strategies For Improved Nitrogen Managementmentioning
confidence: 95%
“…Although the nitrapyrin treatment did not result in an economic advantage for the spring and split N application treatments, the results indicate that for farmers who continue to fall‐apply N, there is a positive economic return for using nitrapyrin. However, a number of other studies have found no significant yield effect nor economic advantage with the use of nitrapyrin (Hendrickson et al, 1978; Touchton et al, 1979; Blackmer and Sanchez, 1988). The variable results with nitrapyrin use are probably due to differences among factors affecting the microbial process of nitrification (e.g., climate and soil type).…”
Section: Strategies For Improved Nitrogen Managementmentioning
confidence: 95%
“…Leafy reduced stature genotypes matured faster, yielded more, and were more tolerant to high planting densities than their conventional counterparts when grown under field conditions in Québec (Begna et al, 1997a; Modarres et al, 1998). As RUE increases with leaf N content (Muchow and Sinclair, 1994) and leaf N content increases with N fertilizer rate (Touchton et al, 1979), an understanding of N fertilization‐hybrid interactions is important.…”
mentioning
confidence: 99%
“…Nitrification of ammonium fertilizers may be partly controlled by granule size. Nitrifrcation capacity in soils can be reduced by nitrapyrin (Touchton et al 1979). …”
mentioning
confidence: 99%